The genetic contribution to severe post-traumatic osteoarthritis. Issue 10 (26th January 2013) - Valdes, Ana M; Doherty, Sally A; Muir, Kenneth R; Wheeler, Margaret; Maciewicz, Rose A; Zhang, Weiya; Doherty, Michael
Abstract : Objective: to compare the combined role of genetic variants loci associated with risk of knee or hip osteoarthritis (OA) in post-traumatic (PT) and non-traumatic (NT) cases of clinically severe OA leading to total joint replacement. Methods: A total of 1590 controls, 2168 total knee replacement (TKR) cases (33.2% PT) and 1567 total hip replacement (THR) cases (8.7% PT) from 2 UK cohorts were genotyped for 12 variants previously reported to be reproducibly associated with risk of knee or hip OA. A genetic risk score was generated and the association with PT and NT TKR and THR was assessed adjusting for covariates. Results: For THR, each additional genetic risk variant conferred lower risk among PT cases (OR=1.07, 95% CI 0.96 to 1.19; p=0.24) than NT cases (OR 1.11, 95% CI 1.06 to 1.17; p=1.55×10 −5 ). In contrast, for TKR, each risk variant conferred slightly higher risk among PT cases (OR 1.12, 95% CI 1.07 to 1.19; p=1.82×10 −5 ) than among NT cases (OR 1.08, 95% CI 1.03 to 1.1; p=0.00063). Conclusions: Based on the variants reported to date PT TKR cases have at least as high a genetic contribution as NT cases.